Litigation friends or foes?: representation of 'P' before the Court of Protection - Ruck Keene, Alex; Bartlett, Peter; Allen, Neil (Oxford University Press, 2016)
This paper argues that, properly analysed, the common law and the European Convention on Human Rights (‘ECHR’) march hand in hand with the provisions of the Mental Capacity Act 2005 (‘MCA 2005’) so as to impose a set of requirements on litigation friends acting for the subject of applications of proceedings before the Court of Protection (‘P’) which are very different to those currently understood by practitioners and the judiciary. The authors examine critically current practice and procedures and provide a set of proposals for reforms.